Formation of research competence of masters of teaching universities in the process of scientific and research practice - Shtonda, Oksana; Biletska, Svitlana; Proskurnia, Oleksii (Scientific notes of the pedagogical department, 2022)
Problem formulation. Research competence should be considered as one of the basic components of the training of masters of professional education, in connection with which it is necessary to implement the principle of double entry of the basic component into the system. The main emphasis should be placed on scientific research practice, the purpose of which is to acquire the skills of a teacher-researcher, to master the modern methods of working with scientific information, its analysis, synthesis, generalization, the ability to work with scientific literature, and the ability to solve pedagogical problems in order to use these abilities, skills, abilities, qualities in professional activity. Thus, during the course of scientific research practice, master’s students will develop research competence. The aim of the article is to study the role of scientific research practice of master’s students of pedagogical higher educational institutions in the formation of research competencies, which are most in demand in the master’s professional activity.Materials and methods. To conduct this research, the following methods were applied in a complex: analysis of psychological-pedagogical and methodical literature, systematization and generalization of diﬀerent views on the formation of research competence in masters of pedagogical universities.Results. The article examines scientific research practice in the master’s degree, defines its goals and objectives, reveals the conditions of its organization and significance in the system of formation of students’ research competence. Attention is paid to the formation of students’ research competencies, first of all at the master’s level and then at the postgraduate level . Research competence is understood as an integrative characteristic of a person, which involves the possession of methodological knowledge, research technology, recognition of their value and readiness to use them in professional activities . Research practice is part of a complex multi-component system of formation of research competence of students in the master’s degree. In the study, the methodological features of conducting scientific-pedagogical practice at master’s degrees are given, and it is found that in the process of scientific-research practice, research competence will be formed in master’s students of pedagogical universities, which will reflect:the graduate’s ability to study, analyze, synthesize scientific literature in the field of professional activity;possessing the skills to optimally choose the methods of scientific research;ability to construct written and oral language in a logically correct, reasoned and clear manner;oratorical abilities, skills of public speaking and competent conversation with opponents;skills in identifying modern problems of professional education and ways to solve them;readiness to work with legislative and educational and regulatory documentation, which is constantly changing;skills of conducting a pedagogical experiment, evaluating and correcting its results;the ability to independently find creative ways to solve non-standard professionalConclusions. Formation of research competence of masters of pedagogical universities implies readiness for innovative professional activity in the field of education. A graduate of the second level of higher education can apply and develop the acquired skills of scientific activity by continuing his studies at the next level - the training of highly qualified personnel, where research competence plays a key role.